2009
DOI: 10.1088/0004-6256/137/2/3414
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution X-Ray Spectroscopy of the Evolving Shock in the 2006 Outburst of Rs Ophiuchi

Abstract: The evolution of the 2006 outburst of the recurrent nova RS Ophiuchi was followed with 12 X-ray grating observations with Chandra and XMM-Newton. We present detailed spectral analyses using two independent approaches. From the best data set, taken on day 13.8 after outburst, we reconstruct the temperature distribution and derive elemental abundances. We find evidence for at least two distinct temperature components on day 13.8 and a reduction of temperature with time. The X-ray flux decreases as a power law, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 63 publications
6
80
0
Order By: Relevance
“…Two recurrent novae with massive WDs of unknown composition were observed using gratings while they were relatively hard X-ray sources. RS Oph did not show very strong lines of Mg and Al, (Nelson et al 2008;Ness et al 2009), consistently with the ultraviolet spectra of a previous outburst (Contini et al 1995). V745 Sco was observed as a hard X-ray source with NuSTAR (Orio et al 2015) and shortly later it was observed it with the Chandra HETG.…”
Section: V959 Mon a Nova Discovered As A Gamma-ray Sourcesupporting
confidence: 85%
“…Two recurrent novae with massive WDs of unknown composition were observed using gratings while they were relatively hard X-ray sources. RS Oph did not show very strong lines of Mg and Al, (Nelson et al 2008;Ness et al 2009), consistently with the ultraviolet spectra of a previous outburst (Contini et al 1995). V745 Sco was observed as a hard X-ray source with NuSTAR (Orio et al 2015) and shortly later it was observed it with the Chandra HETG.…”
Section: V959 Mon a Nova Discovered As A Gamma-ray Sourcesupporting
confidence: 85%
“…This can be approximated by a multi-temperature model or by integration over a continuous temperature distribution. A comparison of these two approaches is presented by Ness et al (2009). The APEC model assumes solar abundances by Anders & Grevesse (1989) that can be scaled by a factor to determine an overall metallicity.…”
Section: Spectral Analysismentioning
confidence: 99%
“…We first analysed the XMM-Newton observation taken on day 14 (ObsID 0410180101), which is not listed in Table 1 because it was not taken during the SSS phase; (Ness et al 2009). We divided the 23 ks observation into 46 overlapping 1000 s time segments but found no significant detection.…”
Section: Rs Ophmentioning
confidence: 99%